Eco-Friendly Pharmaceutical Analysis of Rifaximin in Tablets by HPLC-MS and Microbiological Turbidimetry - Kogawa, Ana Carolina [UNESP]; Mendonça, Jacqueline Nakau; Lopes, Norberto Peporine; Salgado, Hérida Regina Nunes [UNESP] (Oxford University Press (OUP), 2021)
Rifaximin, an antimicrobial used for the treatment of various diseases, lacks analytical methods in official compendia for evaluation of the final product. This paper presents an eco-friendly protocol for rifaximin tablets by high performance liquid chromatography coupled with mass spectrometry (HPLC-MS). The method was completely validated according to the International Conference on Harmonization guidelines and developed following the concept of Quality by Design. The separation was achieved using a C18 column, purified water +0.1% glacial acetic acid and ethyl alcohol, 52:48 (v/v), as mobile phase, 0.9 mL min-1 at 290 nm and ambient room temperature. Mass spectral analyses were performed using electrospray ionization (ESI) ion source and ion trap mass analyzer. The method was linear over the concentration range of 5-50 μg mL-1. The sample was subjected to acidic, basic, neutral, oxidative and photolytic degradation. Degradation products did not interfere in the quantification of the rifaximin, so the method can be considered indicative of stability. Degradation products were also evaluated individually by microbiological method using Escherichia coli. The validated method could be used promisingly as green analytical strategies for detection and quantification of rifaximin in tablets.